Discussion of “Communicated Values as Informal Controls: Promoting Quality While Undermining Productivity?” - Lynn Hannan, R. (Contemporary Accounting Research, 2016)
Abstract Kachelmeier, Thornock, and Williamson ( ) investigate experimentally whether an employer's value statement can affect the way employees cognitively represent how they should approach a multi‐attribute task, and therefore performance. Counter‐intuitively, but consistent with their theory, they find that the value statement negatively affects performance for piece‐rate incentivized participants. In my discussion, I elaborate on my comments from the 2013 CAR Conference. Specifically, I discuss contexts where a firm's value statement may have positive effects on performance, and the importance of conducting research investigating how the decisions made by management accountants affect learning.